2012
DOI: 10.1166/jctn.2012.2051
|View full text |Cite
|
Sign up to set email alerts
|

An Ab Initio Study of Atomic Hydrogen and Oxygen Adsorptions on Armchair Silicon Nanotubes

Abstract: First principles calculations based on hybrid density functional theory have been used to study the electronic and geometric properties of armchair silicon nanotubes from (4 4) to (12 12). Full geometry and spin optimizations have been performed without any symmetry constraints with an all electron 3-21G * basis set and the B3LYP functional. The largest silicon nanotube studied has a cohesive energy of 3.47 eV/atom. Atomic hydrogen and oxygen adsorptions on a Si(6 6) tube have been studied by optimizing the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…The Si-Si bond lengths for the Si(3,3) are 2.25-2.27 Å with a diameter of about 6.51 Å. In addition, the total length of the Si (3,3) in this paper is about 15.62 Å (the main geometrical parameters are shown in Table 1). These results are in good agreement with other studies for SiNTs through hydrogen atoms termination.…”
Section: Electronic and Transport Properties Of Armchair And Zigzag S...mentioning
confidence: 71%
See 2 more Smart Citations
“…The Si-Si bond lengths for the Si(3,3) are 2.25-2.27 Å with a diameter of about 6.51 Å. In addition, the total length of the Si (3,3) in this paper is about 15.62 Å (the main geometrical parameters are shown in Table 1). These results are in good agreement with other studies for SiNTs through hydrogen atoms termination.…”
Section: Electronic and Transport Properties Of Armchair And Zigzag S...mentioning
confidence: 71%
“…Hence, the electronic band structures of the Si(3,3) near the Fermi level together with the projected density of states (PDOS) approach have been calculated and are presented in Fig. 3 showing the conducting properties of Si (3,3). Moreover, there are other several bands near the Fermi level until AE1 eV, and they will contribute greatly to the charge transport of Si (3,3) through the introduction of a bias voltage.…”
Section: Electronic and Transport Properties Of Armchair And Zigzag S...mentioning
confidence: 99%
See 1 more Smart Citation
“…As distinct from the binding energy (−0 543 eV), the strong interaction of Al with B 24 N 24 leads to significant electron transfer from the metal to the B 24 N 24 nanocage. [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] Table I shows the levels of energy for the empty B 24 N 24 and the endohedral B 24 N 24 nanocages. It was clearly found that the empty B 24 N 24 nanocage does not show the effects of spin splitting so the gap of energy between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of B 24 N 24 is the same (4.431 eV) for the majority spin or the minority spin.…”
Section: Resultsmentioning
confidence: 99%
“…SiNTs are promising candidates for the next-generation materials of micro- and nano-electronic devices [ 32 , 33 , 34 ], as they have, for example, better performance with respect to electronic transport [ 35 ], and they are able to produce a current of about one order of magnitude higher than CNTs [ 36 ]. SiNTs have been obtained for the first time from thin solid Si films in 2001 and have directly been synthesized by chemical vapor deposition in 2002 [ 37 , 38 ], and later by molecular beam epitaxy on porous alumina and by self-organized growth of SiNTs with smaller diameter via hydrothermal synthesis [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%